Elemental compositions of sea urchin larval cell vesicles evaluated by cryo-STEM-EDS and cryo-SEM-EDS. (1st January 2023) - Kahil, Keren; Kaplan-Ashiri, Ifat; Wolf, Sharon G; Rechav, Katya; Weiner, Steve; Addadi, Lia
Abstract: During spicule formation in sea urchin larvae, calcium ions translocate within the primary mesenchymal cells (PMCs) from endocytosed seawater vacuoles to various organelles and vesicles where they accumulate, and subsequently precipitate. During this process, calcium ions are concentrated by more than three orders of magnitude, while other abundant ions (Na, Mg) must be removed. To obtain information about the overall ion composition in the vesicles, we used quantitative cryo-SEM-EDS and cryo-STEM-EDS analyzes. For cryo-STEM-EDS, thin (500 nm) frozen hydrated lamellae of PMCs were fabricated using cryo-focused ion beam-SEM. The lamellae were then loaded into a cryo-TEM, imaged and the ion composition of electron dense bodies was measured. Analyzes performed on 18 Ca-rich particles/particle clusters from 6 cells contained Ca, Na, Mg, S and P in different ratios. Surprisingly, all the Ca-rich particles contained P in amounts up to almost 1:1 of Ca. These cryo-STEM-EDS results were qualitatively confirmed by cryo-SEM-EDS analyzes of 310 vesicles, performed on high pressure frozen and cryo-planed samples. We discuss the advantages and limitations of the two techniques, and their potential applicability, especially to study ion transport pathways and ion trafficking in cells involved in mineralization. Statement of significance: The 'inorganic side of life', encompassing ion trafficking and ion storage in soft tissues of organisms, is a generally overlooked problem. Addressing such a problem becomes possible through the application of innovative techniques, performed in cryogenic conditions, which preserve the tissues in quasi-physiological state. We developed here a set of analytical tools, cryo-SEM-EDS, and cryo-STEM-EDS, which allow reconstructing the ion composition inside vesicles in sea urchin larval cells, on their way to deposit mineral in the skeletons. The techniques are complex, and we evaluate here the advantages and disadvantages of each technique. The methodologies that we are developing here can be applied to other cells and other pathways as well, eventually leading to quantitative elemental analyzes of tissues under cryogenic conditions. Graphical abstract: Image, graphical abstract